1999
DOI: 10.1007/bf01007573
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen stable isotopic composition of leaves and soil: Tropical versus temperate forests

Abstract: Several lines of evidence suggest that nitrogen in most tropical forests is relatively more available than N in most temperate forests, and even that it may function as an excess nutrient in many tropical forests. If this is correct, tropical forests should have more open N cycles than temperate forests, with both inputs and outputs of N large relative to N cycling within systems. Consequent differences in both the magnitude and the pathways of N loss imply that tropical forests should in general be more 15N e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
2
19

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(167 citation statements)
references
References 53 publications
12
134
2
19
Order By: Relevance
“…In the soil N of most of these forests, Schuur and Matson (6) have observed the high 15 N͞ 14 N characteristic of the mean of the tropical forest biome (2). Moreover, they observed that the integrated 15 N͞ 14 N of the top 50 cm of soils decreased with MAP, with the steepest change occurring between the sites with 3,350 and 4,050 mm of MAP (Fig.…”
mentioning
confidence: 91%
“…In the soil N of most of these forests, Schuur and Matson (6) have observed the high 15 N͞ 14 N characteristic of the mean of the tropical forest biome (2). Moreover, they observed that the integrated 15 N͞ 14 N of the top 50 cm of soils decreased with MAP, with the steepest change occurring between the sites with 3,350 and 4,050 mm of MAP (Fig.…”
mentioning
confidence: 91%
“…A number of studies have used 15 N natural abundance to determine whether late-successional legumes actively fix N-an approach made feasible by the fact that non-fixing plants in many tropical forests are substantially enriched in 15 N as a consequence of their open N cycle [64]. In most sites, 15 N natural abundance studies suggest that only a small fraction of canopy legumes are actively fixing N-even though many of them belong to genera that are known to nodulate and fix N under appropriate conditions [64][65][66]. An independent approach showed that very little symbiotic BNF was needed to balance N losses in an Amazonian forest [67].…”
Section: From Patterns To Ecological Controlsmentioning
confidence: 99%
“…This result indicates that the three sites are characterized by an open nitrogen cycle (Martinelli et al, 1999), and that denitrification promotes the accumulation of the heavier isotope of N. This accumulation is also reflected in the isotopic composition of plants leaves as discussed below.…”
Section: Soilsmentioning
confidence: 67%
“…Analysis of 13 C was intended to evaluate drought stress and water use efficiency (Farquhar et al, 1982;Lin and Sternberg 1992) whereas 15 N analysis was expected to indicate availability of mineral N in the soil and openness of the N cycle in the system (Martinelli et al, 1999).…”
Section: N)mentioning
confidence: 99%